KERAGAMAN GENETIK DRINGO (Acorus calamus L.) YANG DIGUNAKAN SEBAGAI TUMBUHAN OBAT PADA BEBERAPA ETNIS DI INDONESIA BERDASARKAN INTER-SIMPLE SEQUENCE REPEATS (ISSR) - Subositi, Dyah; Mujahid, Rohmat; Widiyastuti, Yuli (Buletin Kebun Raya, 2015)
Dringo (Acorus calamus L.) used as medicinal plant in Indonesian ethnic groups. Those information based on Ristoja 2012 research. The objective of Ristoja was to provide a database of local ethnomedicine knowledge, herbal formula and medicinal plant in Indonesia. Inter Simple Sequence Repeats (ISSR) markers were used to assess the genetic diversity of Dringo from 20 selected ethnic groups in Indonesia. Ten selected ISSR primers generated 82 amplified fragments with 51,2% were polymorphic. Dice coefficient was used to calculate similarity index and UPGMA was used to construct a dendogram. The genetic similarity index among accessions ranged from 76,7-100% thus indicating that low level of genetic diversity in dringo. Genetic diversity database can be useful for medicinal plant mapping and conservation especially for in situ conservation.